First-principles investigation on multiferroic properties of BiFeO3-REMnO3 (RE = Er, Eu, Gd, Ho, La, Tb). (December 2021) - Ait Tamerd, Mohamed; EL Kassaoui, Majid; Abraime, Brahim; Marjaoui, Adil; El Marssi, Mimoun; Benyoussef, Abdelilah; El Kenz, Abdallah; Lahmar, Abdelilah
Abstract: Structural and multiferroic properties of BiFeO3 -REMnO3 solid solution (RE = Er, Eu, Gd, Ho, La, Tb) have been investigated using the first-principle calculations. Simultaneous substitution of Gd and Mn in BiFeO3 of 12.5% has been carried out. We found that the total magnetic moment in BiFeO3 -REMnO3 is decisively governed by the magnetic moments of rare-earth elements. Our calculations achieved a total magnetic moment of 3.58, 4.69, 5.8, 4.27, 1.5 and 6.31μB in BiFeO3 -REMnO3 for RE = Er, Eu, Gd, Ho, La and Tb, respectively. The calculated total densities of states for all studied materials are clearly asymmetrical with metal characteristics. Further, a pseudo Jahn−Teller distortion was predicted for BiFeO3 -GdMnO3 with the changes in the octahedral tilting angle θ which is responsible for higher magnetization in this system. The spontaneous polarization of BiFeO3 -REMnO3 systems was determined by berry phase methods. The obtained results are close to the experimental and other theoretical results. Graphical Abstract: ga1 Highlights: BiFeO3 -REMnO3 was investigated by First-principles. Pseudo Jahn−Teller distortion was predicted in BiFeO3 -GdMnO3 . Spontaneous polarization of BiFeO3-REMnO3 was determined by berry phase method.